PENGARUH TERAPI CORE STABILITY EXERCISE TERHADAP PENURUNAN TINGKAT NYERI PADA PASIEN LOW BACK PAIN DI WILAYAH KERJA PUSKESMAS GERUNG LOMBOK BARAT - I Gusti Ayu Mirah Adhi; Ni Nyoman Santi Tri Ulandari; Suhartiningsih; Nurhayati; Sri Masdiningsih Utami (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2025)
Low Back Pain (LBP) is a prevalent musculoskeletal disorder and a significant public health concern in Indonesia. The prevalence LBP in Indonesia rangers from 7.6% to 37% total of population. Nonpharamacological management of LBP includes various therapeutic approaches, one of which is Core Stabillity Exercise. CSE isa commonly recognited rehabilitation modality for LBP, aimed at restoring the anatomical and biomechanical function of core muscles.This study to examine the effect of Core Stability Exercise Therapy on pain reduction in patient with Low Back Pain within the working area of Gerung Public Health Center of West Lombok. This present study employed an experimental reserch design that consisted of 88 individuals as population, from which 29 participants were selected as a sample using purposive sampling technique. Inclusion criteria included individuals experiencing mild to moderate LBP, aged 20-59 years, and willing to participate as respondents. The intervention consisted of a pre-test assessment, implementation of Core Stability Exercise therapy, and a post-test evaluation. Data collection was conducted using questionnaires and observational sheets. The results were analyzed using the Wilcoxon signed-rank test. Prior to the intervention, among the 29 respondents, 26 individuals (90%) had experienced mild pain, while 3 individuals (10%) reported had suffered from moderate pain. Following the implementation of Core Stability Exercise therapy. Core Stability Exercise therapy, 20 respondents (69%) reported mild pain, while 9 respondents (31%) reported no pain. Statistical analysis using the Wilcoxon test yielded a p-value of 0.000 (p < 0.05), indicating a significant reduction in pain levels after the intervention. The current findings show that Core Stability Exercise therapy has a significant effect on reducing pain levels in Low Back Pain patients in the working area of Gerung Public Health Center. CSE serves as a safe and accessible alternative therapy that can be performed independently by LBP patients to alleviate lower back pain.